2020
DOI: 10.3892/etm.2020.8930
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑21 regulates the proliferation of placental cells via FOXM1 in preeclampsia

Abstract: The present study determined the expression of microRNA (miRNA or miR)-21 and forkhead box M1 (FOXM1) in placenta and blood samples from patients with preeclampsia (PE), and investigated the relationship between miR-21 and FOXM1. A total of 32 pregnant women with PE and 28 healthy pregnant women were included in the study as the experimental and control groups, respectively. Placental tissues and peripheral blood were collected from all subjects. ELISA was performed to measure the level of FOXM1 protein in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Even more importantly, we cannot forget that the expression of almost all of these miRNAs has also been conveyed in pregnancy-associated disorders. For example, miR-21, miR-29, miR-150 and miR-155 are highly expressed in human placentae of preeclampsia patients [ 44 , 45 , 46 ]; aberrant expression of miR-21 was reported to be associated with foetal hypoxia, foetal growth restriction, and macrosomia [ 47 , 48 , 49 ]; mir-29, miR-98 were upregulated in placentas from gestational diabetes mellitus patients [ 50 , 51 ]. For all these reasons, although the induction of these miRNAs has been associated with an effective control of viral replication, and no SIPW enrolled in this study had obstetric pathology related to placental malfunction, we cannot exclude that the alteration of miRNA profile might result from pregnancy-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Even more importantly, we cannot forget that the expression of almost all of these miRNAs has also been conveyed in pregnancy-associated disorders. For example, miR-21, miR-29, miR-150 and miR-155 are highly expressed in human placentae of preeclampsia patients [ 44 , 45 , 46 ]; aberrant expression of miR-21 was reported to be associated with foetal hypoxia, foetal growth restriction, and macrosomia [ 47 , 48 , 49 ]; mir-29, miR-98 were upregulated in placentas from gestational diabetes mellitus patients [ 50 , 51 ]. For all these reasons, although the induction of these miRNAs has been associated with an effective control of viral replication, and no SIPW enrolled in this study had obstetric pathology related to placental malfunction, we cannot exclude that the alteration of miRNA profile might result from pregnancy-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on the association between miR-21 expression and PE presented inconsistent results. Some studies reported overexpression of miR-21 in PE placentas [ 47 , 48 ], and also in maternal plasma or serum of PE patients [ 43 , 48 ]. Results of the study by Jairajpuri et al (2017) depicted upregulation of circulating miR-21 in the plasma of patients with severe PE compared to the mild form [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-21 in preeclampsia has been also newly studied, since it regulates the forkhead box M1 protein (FOXM1), which is expressed in cytotrophoblasts for proliferation and differentiation, responsible for the early placental development [ 93 ]. In fact, a study showed that miR-21 is elevated with reduced FOXM1 expression in patients with preeclampsia compared to those in normotensive pregnant women, implying that miR-21 may impede the early placental invasion leading to preeclampsia [ 94 ]. These results demonstrate that various miRNAs are involved in the pathway of preeclampsia which implies their potential to become possible future therapeutic targets for treatment of preeclampsia.…”
Section: Molecular Factors Resulting From Inadequate Uteroplacental Perfusion Leading To Preeclampsiamentioning
confidence: 99%